Effects of Linguistic Challenges on Ghanaian Pre-Service Teachers’ Self-Efficacy Beliefs in English Medium Instruction - Dzormeku, Charles (My University, 2023)
This study attempts to categorize Ghanaian pre-service teachers according to their levels of English language linguistic challenges and investigates the relationship between their Core English language grades and their linguistic challenges. It further explored the relationships between the self-efficacy belief levels of these groups with reference to their EMI linguistic challenges. Adopting the sequential mixed method, a total of 300 participants were surveyed in the Ashanti region of Ghana, followed by eight interviews. A 45-item EMI challenges instrument (Aizawa et al., 2020) and the short form of the Teachers’ Sense of Efficacy Scale (Tschannen-Moran & Hoy, 2001) were employed. Qualitative data were also collected using semi-structured interviews based on the findings of the quantitative analysis. Descriptive statistical analysis indicated that writing was the most challenging of the four language skills for participants. Moreover, the prevailing evidence testifies that limited vocabulary, inability to develop coherent paragraphs, pronunciations, and orthographic as well as grammatical inaccuracies are the paramount challenges that participants face. A Latent Profile Analysis revealed four groups with different levels of EMI linguistic challenges among the participants. ANOVA also indicated that the higher the EMI linguistic challenges of a group, the lower their self-efficacy beliefs. It is recommended that English be taught throughout the four-year duration of teacher education programs. Further research should be conducted to identify effective pedagogical approaches to enhance English language acquisition from the basic school level to higher education level.
Keywords: English Medium Instruction, West African Senior Secondary School Certificate Examination (WASSCE), language skills, pre-service teacher, teacher self-efficacy beliefs